Understanding Disturbance Regimes From Patterns in Modeled Forest Biomass - Wang, Siyuan (2024)
Funding Information: The authors express their gratitude to the Associate Editor and two anonymous Reviewers for their constructive feedback on a first version of the manuscript. SW acknowledges support from the International Max Planck Research School for Biogeochemical Cycles (IMPRS\u2010gBGC). SW and HY acknowledge EEBIOMASS, Project Office BIOMASS, support from the German Federal Ministry of Economics and Technology (50EE1904). Open Access funding enabled and organized by Projekt DEAL. Publisher Copyright: © 2024 The Authors. Journal of Advances in Modeling Earth Systems published by Wiley Periodicals LLC on behalf of American Geophysical Union.